2006
DOI: 10.1093/gerona/61.4.367
|View full text |Cite
|
Sign up to set email alerts
|

A System of Integrated Care for Older Persons With Disabilities in Canada: Results From a Randomized Controlled Trial

Abstract: Integrated systems appear to be feasible and have the potential to reduce hospital and nursing home utilization without increasing costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
222
0
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(236 citation statements)
references
References 23 publications
1
222
0
13
Order By: Relevance
“…The second is at the point of care delivery. For example, the Frail Aged MDT review noted the role of geriatric assessment developed by a multidisciplinary team (Beland, Bergman, Lebel, & Clarfield, 2006) where the COPD review discussed the role of the multidisciplinary palliative care team including the GP in managing patient needs in dyspnoea (Rabow, Dibble, Pantilat, & McPhee, 2003).…”
Section: Narrative Summary Of Common Findings From Individual Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second is at the point of care delivery. For example, the Frail Aged MDT review noted the role of geriatric assessment developed by a multidisciplinary team (Beland, Bergman, Lebel, & Clarfield, 2006) where the COPD review discussed the role of the multidisciplinary palliative care team including the GP in managing patient needs in dyspnoea (Rabow, Dibble, Pantilat, & McPhee, 2003).…”
Section: Narrative Summary Of Common Findings From Individual Reviewsmentioning
confidence: 99%
“…This heterogeneity also created problems in assessing the applicability to the Australian context. For example, the MDT frail aged review highlights that frailty may not necessarily be solely the function of chronological age (Beland et al, 2006;Rockwood et al, 2005). Study designs that drew upon care interventions within a health maintenance organisation (HMO) need to be considered in terms of their generalisability to Australia with a universal health coverage system (Beland et al).…”
Section: Narrative Summary Of Common Findings From Individual Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Projects implementing integrated care have taken centre stage as a way to improve quality and efficiency in care for the elderly [3,5]. But adoption of these integrated care models generates implementation problems, and it is difficult to secure the participation of professionals, particularly that of general practition ers (GPs) [6][7][8]. While GP participation represents one of the key success factors in the implementation of integrated care models [9,11], research has found a lag between the conceptual approach of these models and professional practice in primary care [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…162-163) The LTC system has to move away from a fragmented, supply-driven towards an integrated, demand-driven system to improve the quality of care and to increase the operational efficiency to assure LTC for everyone (e.g. Béland, et al, 2006;Beukema & Valkenburg, 2007;De Blok et al, 2009;van den Bosch, 2010). An integrated care system is defined as "an organized, coordinated, and collaborative network that links various care providers to provide a coordinated, vertical continuum of services to a particular patient population or community" (Enthoven, 2009, p. 284).…”
Section: The Transition Of the Ltc Systemmentioning
confidence: 99%